DIALECTICS OF RIGHTS AND DUTIES IN THE LEGAL AXIOLOGY OF RUSSIAN CONSERVATISM OF THE 19TH CENTURY - Kuzubova, Angelina; Podoksenov, Alexander; Savvina, Olga; Shabalina, Evgeniya; Goryunova, Elena (Revista Inclusiones, 2019)
Turning to the study of the relationship and interaction of rights and duties in the political and legal doctrine of domestic conservatism seems relevant due to the presence of problems in legal regulation due to the lack of formation of the system of legal values, the confrontation of their groups in the modern legal culture of Russia. Despite its importance, the axiological potential of duties in the conservative dimension remains little studied. An attempt is presented to analyze the phenomenon of duties, which is perceived differently in the liberal and conservative political and legal doctrines of the 19th century. The views of leading conservative thinkers of the prerevolutionary period are examined: M.N. Katkov, the ideologists of Slavophilism I.S. Aksakova, A.S. Khomyakova, conservatives of the second half of the XIX century N.Ya. Danilevsky, K.N. Leontiev, K.P. Pobedonostseva, L.A. Tikhomirova, made an appeal to the heritage of I.A. Ilyin, related to the first quarter of the XX century, etc. It is concluded that the political and legal doctrine of conservatism in the context of the religious doctrine of human sinfulness questioned the absolutization of human rights, justified the primacy of duties over rights. Russian conservatism of the 19th century put forward the theory of moral law, raising the functional of law over state coercion, affecting the motives of legal behaviour, lying outside the fear of coercion by the authorities in this theory, the convergence of moral duty and legal duty was embodied in legal moral duty, which had attributive signs of two phenomena.